Spiritual letters in print. The cases of Vittoria Colonna and Paola Antonia Negri (Prassi Ecdotiche della Modernità Letteraria, 2020)
The essay considers the editorial history of two publications of spiritual letters, printed in the 16th century under the names of Vittoria Colonna and Paola Antonia Negri. This perspective aims to highlight the peculiar philological problems of these editions, connected to some practices of intervention on the texts that are substantial for religious writings edited without the direct supervision of the author.